Implementation Of Reversible Logics On Combinational Circuits For Optimum Performance - et. al., Dr. D. Jessintha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, reversible gate has emerged as most exciting research mission for least power loss circuit design, with applications towards low power CMOS, cryptography and image processing .Also in nanotechnology, this proposal introduces a novel and quantum cost effective reversible complete adder circuit . This gate which is proposed is used as a reversible complete adder device on its own. It isverified that the proposed gate has less hardware configuration than its current counterparts.The researchers' theoretical minimum is also met by the proposed reversible multiplier.In comparison to the previous design, the new design has shown to be more successful.